Prenatal Diagnosis and Risk Factors for Preoperative Death in Neonates with Single Right Ventricle and Systemic Outflow Obstruction: Screening Data from the Pediatric Heart Network Single Ventricle Reconstruction Trial - Atz, Andrew M. (2010)
OBJECTIVES: The purpose of this analysis was to assess preoperative risk factors prior to the first-stage Norwood surgery in infants with hypoplastic left heart syndrome and related single ventricle lesions, and to evaluate practice patterns in prenatal diagnosis as well as the role of prenatal diagnosis in outcome. METHODS: Data from all live births with morphologic single right ventricle and systemic outflow obstruction screened for the Pediatric Heart Network Single Ventricle Reconstruction Trial were used to investigate prenatal diagnosis and preoperative risk factors. Demographics, gestational age, prenatal diagnosis status, presence of major extracardiac congenital abnormalities and preoperative mortality rates were recorded. RESULTS: Of 906 infants, 677 (75%) had prenatal diagnosis, 15% were preterm (<37 weeks), and 16% were low birth weight (<2500 g). Rates of prenatal diagnosis varied by study site (59%-85%, p<0.0001). Major extracardiac congenital abnormalities were less prevalent in those born after prenatal diagnosis (6% vs. 10%, p=0.03). There were 26 (3%) deaths prior to Norwood palliation; preoperative mortality did not differ by prenatal diagnosis status (p=0.49). In multiple logistic regression models, preterm birth (p=0.02), major extracardiac congenital abnormalities (p<0.0001), and obstructed pulmonary venous return (p=0.02) were independently associated with preoperative mortality. CONCLUSIONS: Prenatal diagnosis occurred in 75%. Preoperative death was independently associated with preterm birth, obstructed pulmonary venous return and major extracardiac congenital abnormalities. Adjusted for gestational age and the presence of obstructed pulmonary venous return, the estimated odds of preoperative mortality were 10 times greater for subjects with a major extracardiac congenital abnormality.